A DEEP DIVE INTO THE SIGNIFICANCE OF TRANSLATION OF PHRASES AND IDIOMS - Maktuba Mahamadaliyevna Khonsaidova; Sodikjon Sobirjonovich Ruzmetov (Western European Studies, 2024)
This article outlines the fundamental aspects of idioms and phrases, relevant connections, and a bit of differentiation from other cultural expressions. It also delves into the significance of translation to express idioms, exploring their importance and examining strategies for effective rendering. This article's main objectives include identifying a phrase and idiom, their usage as a part of speech, its connection with independent clauses, and depicting some essential common types. There is a great motive related to phrase (the main illustration and root of the idioms), its cultivation through the intercultural appearance, linguistic relevance, and differentiation of forming as a part of speech or sentence in all language grammar functions. Furthermore, an idiom is a meaningful and vital expression as well as the main part of a phrase that everyone might not comprehend straightforwardly by identifying the meaning by using single words. It is highly proven that idioms are the basic part of the word structure that defines the semantics, linguistics, and pragmatic functions of the communicative approach that logically conveys the word expression. Idioms are a group of words that have a meaning based on the essence of the words. It is used in everyday conversation. People tend to express their happenings in idioms to deliver important, valuable sayings, just as an example of something worth sharing or talking about.
Keywords: idioms; phrase; linguistics